SURVEI KONDISI FISIK PEMAIN PADA CABANG OLAHRAGA FUTSAL - Rahman, Arbain; Rubiyatno, Rubiyatno; Sastaman, Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Physical condition is closely related to futsal sports, there are 3 instruments in this study, namely endurance which is used to measure the ability to carry out prolonged physical activity and withstand fatigue for 2x20 minutes in futsal sports, player agility because this is a person's ability to change body position quickly and precisely by controlling movement, balance and coordination, and speed of a futsal player because it increases the player's running or when dribbling the ball. The method used in this research is a survey method, while the data collection technique uses tests and measurements. The population in this study were extracurricular futsal players at SMAN 3 Sanggau, while the sample used in this research was extracurricular futsal players at SMAN 3 Sanggau, totaling 14 people. The instruments used are; (1) Endurance is measured using the Harvard Step Test. (2) agility was measured using the Illinois Agility test (3) speed was measured using the 30 meter spirit test. Data analysis uses descriptive percentages. The results of the analysis of the 3 physical condition test instruments for extracurricular futsal players at SMAN 3 Sanggau which were carried out obtained the following results, the majority of scores were very good here, namely the agility test in the "Very Good" category, 5 people (36%). Meanwhile, for the majority of results, the score that is very poor here is the endurance test with the category "Very Poor" 3 people (21%). influenced by factors, namely sleep and rest, and smoking habits.